Magnetospheric Substorms and Discrete Arcs of the Polar Aurora - Stepanova, M (2012)
A brief review of the results of the research in physics of the Earth s magnetosphere leading to a substantial modification of the previously developed approaches is presented. The main emphasis is placed on physics of magnetospheric substorms and the nature of auroral arcs. It is shown that the formation of powerful electron beams that produce multiple arcs can be associated with the penetration of cold electrons of an ionospheric origin into the region of field-aligned acceleration of hot magnetospheric electrons. © 2012 Allerton Press, Inc.